2016
DOI: 10.1039/c6cp01680d
|View full text |Cite
|
Sign up to set email alerts
|

Protecting and accelerating adiabatic passage with time-delayed pulse sequences

Abstract: Using numerical simulations of two-photon electronic absorption with femtosecond pulses in Na2 we show that: i) it is possible to avoid the characteristic saturation or dumped Rabi oscillations in the yield of absorption by time-delaying the laser pulses; ii) it is possible to accelerate the onset of adiabatic passage by using the vibrational coherence starting in a wave packet; and iii) it is possible to prepare the initial wave packet in order to achieve full state-selective transitions with broadband pulses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…6(a). 12 The wave packet is prepared as a superposition of the first n c vibrational levels in the ground state. The amplitudes and phases of the wave packet are optimized to maximize the yield of absorption in the A band at the end of the pulse using the Geometrical Optimization approach.…”
Section: Results In Namentioning
confidence: 99%
See 2 more Smart Citations
“…6(a). 12 The wave packet is prepared as a superposition of the first n c vibrational levels in the ground state. The amplitudes and phases of the wave packet are optimized to maximize the yield of absorption in the A band at the end of the pulse using the Geometrical Optimization approach.…”
Section: Results In Namentioning
confidence: 99%
“…10,11 This can be beaten by working with very short pulses, demanding even stronger pulses. 12 Under strong fields, a plethora of new phenomena occur in molecules. Aside from ionization or other multiphoton processes, the potential energy surfaces change due to dynamic Stark shifts, dramatically affecting the resonances and photophysics of the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because of intramolecular vibrational redistribution (IVR) and conical intersections (or other nonadiabatic couplings) one typically needs to move the population rapidly through the transition state, which favors doing it in the absence of a barrier in the excited state. Using strong fields to drive the electronic absorption leads naturally to study the effect of vibrational motion (or vibrational coherence) to enhance such absorption. Recent results in two-photon processes (such as a pump-dump mechanism) have shown that the optimization of the initial wave packet is less important when the pulses are time-delayed . In this work we investigate its role in isomerization reactions, with the wider goal of finding new mechanisms to enhance the yield and especially accelerate the rate of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Using strong fields to drive the electronic absorption leads naturally to study the effect of vibrational motion (or vibrational coherence) to enhance such absorption [59][60][61][62][63][64][65][66][67]. Recent results in two-photon processes (such as a pump-dump mechanism) have shown that the optimization of the initial wave packet is less important when the pulses are time-delayed [68]. In this work we investigate its role in isomerization reactions, with the wider goal of finding new mechanisms to enhance the yield and especially accelerate the rate of the reaction.…”
Section: Introductionmentioning
confidence: 99%